Orally administrated chitosan microspheres bind Helicobacter pylori and decrease gastric infection in mice. (15th September 2020) - Henriques, Patrícia C.; Costa, Lia M.; Seabra, Catarina L.; Antunes, Bernardo; Silva-Carvalho, Ricardo; Junqueira-Neto, Susana; Maia, André F.; Oliveira, Pedro; Magalhães, Ana; Reis, Celso A.; Gartner, Fátima; Touati, Eliette; et al.
Abstract: Persistent Helicobacter pylori ( H. pylori ) infection is related to 90% of gastric cancers. With bacterial resistance rising and treatment inefficiency affecting 15% of the patients, alternative treatments urge. Chitosan microspheres (ChMics) have been proposed as an H. pylori -binding system. This work evaluates ChMics biocompatibility, mucopenetration and capacity to treat H. pylori infection in mice after oral administration. ChMics of different size (XL, ∼120 µm and XS, ∼40 µm) and degree of acetylation (6% and 16%) were developed and revealed to be able to adhere both human and mouse-adapted H. pylori strains without cytotoxicity towards human gastric cells. Ex vivo studies showed that smaller (XS) microspheres penetrate further within the gastric foveolae, suggesting their ability to reach deeply adherent bacteria. In vivo assays showed 88% reduction of infection when H. pylori -infected mice (C57BL/6) were treated with more mucoadhesive XL6 and XS6 ChMics. Overall, ChMics clearly demonstrate ability to reduce H. pylori gastric infection in mice, with chitosan degree of acetylation being a dominant factor over microspheres' size on H. pylori removal efficiency. These results evidence the strong potential of this strategy as an antibiotic-free approach to fight H. pylori infection, where microspheres are orally administered, bind H. pylori in the stomach, and remove them through the gastrointestinal tract. Statement of Significance: Approximately 90% of gastric cancers are caused by the carcinogenic agent Helicobacter pylori, which infects >50% of the world population. Bacterial resistance, reduced antibiotic bioavailability, and the intricate distribution of bacteria in mucus and within gastric foveolae hamper the success of most strategies to fight H. pylori . We demonstrate that an antibiotic-free therapy based on bare chitosan microspheres that bind and remove H. pylori from stomach can achieve 88% reduction of infection from H. pylori -infected mice. Changing size and mucoadhesive properties, microspheres can reach different areas of gastric mucosa: smaller and less mucoadhesive can penetrate deeper into the foveolae. This promising, simple and inexpensive strategy paves the way for a faster bench-to-bedside transition, therefore holding great potential for clinical application. Graphical abstract: Image, graphical abstract